Modern trends in the optimization of managerial processes at manufacturing enterprises - I. A. Guzhin (Путеводитель предпринимателя, 2025)
This article examines trends in the optimization of managerial processes in manufacturing organizations. These enterprises face the need for continuous management improvement in the context of digitalization and global competition. The relevance of the topic is determined by the fact that traditional methods often lose their effectiveness, necessitating the implementation of new technologies, adaptive approaches, and the integration of various optimization systems. Despite a significant number of studies dedicated to this issue, the scientific community still debates the priority directions of optimization: some authors emphasize digital solutions and automation, others focus on flexible management schemes, while a third group highlights lean manufacturing and economic security. The objective of this study is to analyze modern trends in this field, with a particular emphasis on the production of sports equipment, and to identify the most effective approaches. The research findings indicate that digitalization, business process modeling, agile management methods, and lean manufacturing tools play a key role in improving the operational efficiency of companies. However, a comprehensive approach that integrates these methods remains insufficiently covered in the literature. The author’s contribution lies in the systematization of existing approaches and their adaptation to the realities of the sports industry, with a focus on practical aspects and recommendations for implementation. The presented materials will be useful both to the academic community engaged in research in the fields of management and production logistics and to practitioners, including industrial enterprise managers, business analysts, and organizational development specialists.